The effect of training on employees’ work performance in civil service organizations - Getahun, Belaynesh Lemma; Yohannes, Mindaye (Journal of Management and Business Education, 2025)
Training plays a vital role in enhancing employee job performance. This study aims to examine the impact of training programs on job performance by analyzing the relationship between training and employee performance. A mixed-methods research approach was adopted, employing both quantitative and qualitative techniques. Specifically, a sequential mixed-methods design was utilized. Qualitative data were collected through purposive sampling, while stratified sampling was used to select participants for the quantitative phase. A total of 405 experts and middle-level managers were surveyed using a simple random sampling technique. Data were analyzed using SPSS, incorporating both descriptive and explanatory research designs. Correlation and regression analyses were conducted to assess the relationship between dependent and independent variables. The findings indicate that training has a statistically significant effect on job performance. However, two dimensions—learning and reaction—were found to be insignificant, while behavior and results emerged as the most influential factors affecting job performance. These results highlight the importance of focusing on behavioral outcomes and performance-based results when designing training programs.